High sensitivity of TiO2 nanorod array electrode for photoelectrochemical glucose sensor and its photo fuel cell application - He, Lihua; Liu, Quanbing; Zhang, Shenjie; Zhang, Xiangtian; Gong, Chunli; Shu, Honghui; Wang, Guangjin; Liu, Hai; Wen, Sheng; Zhang, Bingqing (Electrochemistry communications, 2018)
Due to the separation of the excitation source and detection signal, the use of photoelectrochemical (PEC) glucose sensors is regarded as a promising electrochemical approach offering high sensitivity for glucose analysis by photoelectrocatalytic oxidation of glucose. In this study, we present a PEC glucose sensor based on TiO2 nanorod array (TiO2NRA) electrode, exhibiting high sensitivity of around 200 μA cm−2 mM−1 in glucose detection for the concentrations in the range of 0.01–0.20 mM. Moreover, the TiO2NRA can be fabricated and used in a photo fuel cell (PFC) to generate electricity. This investigation expands the applications of TiO2 and provides a high sensitive way for glucose sensing. [Display omitted] •A non-enzymatic photoelectrochemical (PEC) glucose sensor was constructed.•The PEC sensor is comprised of TiO2 NRA electrode, without any other catalysts.•High sensitivity of 201.5 μA cm−2 mM−1 in glucose detection for the concentrations in the range of 0.01–0.20 mM•Electricity can be generated by photo-oxidizing glucose on TiO2NRA in a photo fuel cell device.•The work expands the applications of TiO2 and provides a high sensitive way for glucose sensing.